Colorblind Racism - Part 1 - Anna Hackman (2018)
Capsule vidéo qui explique le racisme aveugle à la race, premier partie.
Keywords: approches et analyses; cours; discipline; intersectionnalité; pol5480; premier cycle; racisme; sciences humaines; sociologie; systèmes d'oppressions; thématiques; violences

Colorblind Racism - Part 2 - Anna Hackman (2018)
Capsule vidéo qui explique le racisme aveugle à la race, deuxième partie.
Keywords: approches et analyses; cours; discipline; intersectionnalité; pol5480; premier cycle; racisme; sciences humaines; sociologie; systèmes d'oppressions; thématiques; violences

Keetsahnak: our missing and murdered Indigenous sisters - Anderson, Kim; Campbell, Maria; Belcourt, Christi (The University of Alberta Press, 2018)
«In Keetsahnak / Our Murdered and Missing Indigenous Sisters, the tension between personal, political, and public action is brought home starkly. This important collective volume both witnesses the significance of the travelling exhibition Walking With Our Sisters and creates a model for antiviolence work from an Indigenous perspective. The contributors look at the roots of violence and how it diminishes life for all. They acknowledge the destruction wrought by colonial violence, and also look at controversial topics such as lateral violence, challenges in working with "tradition," and problematic notions involved in "helping." Through stories of resilience, resistance, and activism, the editors give voice to powerful personal testimony and allow for the creation of knowledge.»-- Provided by publisher.
Keywords: activisme; amériques; anti-violence; approches et analyses; canada; cours; droits des femmes*; droits des femmes* autochtones; féminicide; féminisme autochtone; histoire et politique; intersectionnalité; militance; pol4105; premier cycle; régions géographiques; résistance; système colonial; systèmes d'oppressions; thématiques; violences

Kiffe ta race - Binge Audio - Ly, Grace; Diallo, Rokhaya (Kiffe ta race - Binge Audio, 2018)
Pourquoi le mot « race » est-il tabou ? Qu’en est-il quand on est, à la fois, victime de discriminations raciales et sexuelles ? Comment assumer son identité plurielle ? Un mardi sur deux, Rokhaya Diallo et Grace Ly reçoivent un·e invité·e pour explorer les questions raciales sur le mode de la conversation et du vécu.
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; afro-féminisme; approches et analyses; care; com5170; communication; corps; cours; discipline; europe; france; identités; intersectionnalité; journalisme; justice sociale; militance; premier cycle; pédagogie; périodes historiques; racisme; régions géographiques; système colonial; systèmes d'oppressions; thématiques; théorie critique de la race; violences